2021
DOI: 10.1038/s41598-020-79161-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparing microfluidics and ultrasonication as formulation methods for developing hempseed oil nanoemulsions for oral delivery applications

Abstract: Emerging formulation technologies aimed to produce nanoemulsions with improved characteristics, such as stability are attractive endeavors; however, comparisons between competing technologies are lacking. In this study, two formulation techniques that employed ultrasound and microfluidic approaches, respectively, were examined for relative capacity to produce serviceable oil in water nanoemulsions, based on hempseed oil (HSO). The ultrasound method reached > 99.5% entrapment efficiency with nanoemulsions th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 37 publications
2
17
0
1
Order By: Relevance
“…However, we observed a slight decrease in the mean (±SD) nanoparticle sizes of TQ-free and TQ-loaded nano-self-assemblies on increasing TFR from 50 to 100 µL/min (Table 1). This is consistent with previous findings [40,45,[59][60][61], and most likely attributed to presence of a relatively higher shear stress at TFR of 100 µL/min, leading to self-assembly of both lipids in the presence of relatively higher concentration of ethanol at the intersection of the center and side microfluidic channels. This is associated with a provision of relatively shorter time for ethanol to diffuse out and mix with excess buffer on increasing TFR from 50 to 100 µL/min [40,45,59].…”
Section: Size Characteristics Of Tq-free and Tq-loaded Citrem/spc Nano Self-assembliessupporting
confidence: 93%
“…However, we observed a slight decrease in the mean (±SD) nanoparticle sizes of TQ-free and TQ-loaded nano-self-assemblies on increasing TFR from 50 to 100 µL/min (Table 1). This is consistent with previous findings [40,45,[59][60][61], and most likely attributed to presence of a relatively higher shear stress at TFR of 100 µL/min, leading to self-assembly of both lipids in the presence of relatively higher concentration of ethanol at the intersection of the center and side microfluidic channels. This is associated with a provision of relatively shorter time for ethanol to diffuse out and mix with excess buffer on increasing TFR from 50 to 100 µL/min [40,45,59].…”
Section: Size Characteristics Of Tq-free and Tq-loaded Citrem/spc Nano Self-assembliessupporting
confidence: 93%
“…The interaction of HSO and whey was a significant factor affecting Z-ave of samples ( p < 0.05). The significant interaction effect of HSO and a poloxamer used as a surfactant to produce an HSO-based nanoemulsion was previously reported [ 36 ]. The ANOVA and the regression analysis also showed that the PDI of nanoemulsion samples could be fit to a linear model with HSO (%) as the only significant factor ( p < 0.05).…”
Section: Resultsmentioning
confidence: 84%
“…PDI values below 0.2 indicate a good stability of the colloid suspension [ 60 ]. For ultrasonication, a decrease in droplet size and PDI of emulsions is created by cavitation with high-energy sound waves [ 61 ], which depends on frequency, amplitude and sonication process [ 62 ].…”
Section: Resultsmentioning
confidence: 99%